2003
DOI: 10.1007/s10162-002-3011-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analyses of the Mouse Deafness Mutations Varitint-Waddler (Va) and Jerker (Espnje)

Abstract: Genetic studies on spontaneous mouse mutants with hearing defects have provided important insights into the function of genes expressed in inner ear hair cells. Here we report on our genetic analyses of the deaf mutants varitint-waddler (Va) and jerker (Espn je ). A high-resolution genetic map localizes Va J to a 0.14 ± 0.08 cM region between D3Mit85 and D3Mit259 on distal chromosome 3. By comparative mapping, the human ortholog resides at 1p22.3 between markers D1S3449 and D1S2252. To study the effect of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…6B), measurements that are in agreement with those in a previous report (15). The results for Mcoln3 ϩ/ϩ ; Atp2b2 dfw/ϩ mice are in accordance with previous findings of no significant differences in comparison with wild-type controls (16).…”
Section: Abr Thresholds For Mcoln3supporting
confidence: 83%
“…6B), measurements that are in agreement with those in a previous report (15). The results for Mcoln3 ϩ/ϩ ; Atp2b2 dfw/ϩ mice are in accordance with previous findings of no significant differences in comparison with wild-type controls (16).…”
Section: Abr Thresholds For Mcoln3supporting
confidence: 83%
“…Concordance between the espin gene and the jerker mutation has been confirmed by detailed physical mapping studies [37,38].…”
Section: Jerker Deafness Mutation In the Mouse Espin Genementioning
confidence: 77%
“…Nonetheless, it has been reported that the Va/+ heterozygotes suffer from hearing loss, vestibular dysfunction (circling behavior, head-bobbing, waddling), and coat color dilution. Meanwhile, the Va J /Va J homozygote mice are also deaf with almost similar coat color dilution as the Va/+ heterozygotes, but for an unknown reason, the Va J /Va J homozygotes appear to have no vestibular defects [4,7,11,17]. Furthermore, the Va J /+ heterozygote mice show a much milder phenotype-exhibiting normal vestibular function, partial hearing, and a very small amount of pigmentation deficiency [4,11].…”
Section: The Varitint-waddler (Va) Phenotypesmentioning
confidence: 91%
“…This is perhaps due to the observed lethality of the homozygous alleles and sterility of progenies that do survive (cited in ref. [4,7,11,17]). Nonetheless, it has been reported that the Va/+ heterozygotes suffer from hearing loss, vestibular dysfunction (circling behavior, head-bobbing, waddling), and coat color dilution.…”
Section: The Varitint-waddler (Va) Phenotypesmentioning
confidence: 97%
See 1 more Smart Citation